PENDIDIKAN LITERASI KEUANGAN BAGI SISWA SMK NEGERI 3 PALEMBANG - Yuliani, Yuliani; Hs Umrie, Rasyid; W Bakar, Samadi (Jurnal Abdimas Musi Charitas, 2020)
Financial literacy education from an early age makes a person organize and plan finances will be better for the future. A person's ability in financial planning is not learned in formal education but this education is very important and inherent individually. Someone who have knowledge about financial planning in the future can be obtained through an education. The purpose of this service was to provide financial knowledge education to students of SMK Negeri 3 Palembang. The form of dedication was counseling and opening up the insights of personal finance since early as a student. This service was held on Wednesday 30 November 2019 at 13.00 pm in the Meeting Room of SMK Negeri 3 Palembang. The results of devotion activities Students of SMK Negeri 3 Palembang understand about financial literacy, smart to manage of finance, investing, saving. The practical implications of this activity Students of SMK Negeri 3 Palembang could to applied the results of activities in daily life including saving lives, creating surplus cash flow.